Forced Migration of Internally Displaced Persons (IDPs) in Ukraine: Current Situation, Problems, Solutions - Novikova Olha F.; Pankova Oksana V. (Problemi Ekonomiki, 2018)
The aim of the article is to highlight the situation and problems concerning the forced migration of internally displaced persons (IDPs) in Ukraine, as well as to suggest ways for addressing the problems. There analyzed the specificity of the forced displacement of the population of Ukraine due to the temporary occupation of the Autonomous Republic of Crimea and certain regions of Donetsk and Luhansk regions, the armed conflict in the east of Ukraine. To conduct the analysis, statistical data, results of the carried out expert survey, research data and reports of international organizations were used. The article discusses the problems encountered by internally displaced persons (IDPs) in connection with the situation of displacement, motives for moving from temporarily occupied territories, data on the length of staying in places of resettlement, and plans for further movement. Attention is focused on the main achievements and shortcomings of the state policy regarding IDPs. The contribution of national civil society institutions and international organizations to the provision of various forms of assistance and support to IDPs is noted. Based on the analysis, a number of directions for improving the state migration policy under conditions of massive forced internal displacement are proposed.